The phenotype of gastric mucosa coexisting with Barrett's oesophagus. Issue 6 (1st June 2001) - Rugge, M; Russo, V; Busatto, G; Genta, R M; Di Mario, F; Farinati, F; Graham, D Y
Abstract : Background/Aims —Barrett's oesophagus complicates the gastro-oesophageal acid reflux. Helicobacter pylori infection, particularly with cagA positive strains, induces inflammatory/atrophic lesions of the gastric mucosa, which may impair acid output. No systematic study has investigated the phenotype of the gastric mucosa coexisting with Barrett's oesophagus. This study was designed to identify the phenotype of gastric mucosa associated with Barrett's oesophagus. Methods —In this retrospective case control study, the phenotype of the gastric mucosa was histologically characterised in 53 consecutive patients with Barrett's oesophagus and in 53 (sex and age matched) non-ulcer dyspeptic controls. Both patients and controls underwent extensive sampling of the gastric mucosa (two antral, one incisural, and two oxyntic biopsies). Intestinal metaplasia (IM) was categorised (type I, complete IM; types II and III, incomplete IM) by the high iron diamine stain; cagA status was ascertained by genotyping. Results—Helicobacter pylori was present in 19 of the 53 patients with Barrett's oesophagus and in 30 of the 53 controls (p < 0.02); eight of the 19 patients with Barrett's oesophagus and 28 of the 35 controls harboured cagA positive H pylori (p < 0.03). The histological severity of non-atrophic gastritis detected in the controls was significantly higher than that detected in the patients with Barrett's oesophagus (p < 0.0001). Multifocal atrophic gastritis was present in 4% of the patients with Barrett's oesophagus and in 23% of controls (p < 0.01). The odds ratio for the association between multifocal atrophic gastritis and Barrett's oesophagus was 0.20 (95% confidence interval, 0.006 to 0.60). Gastric IM was detected in 13.2% of the patients with Barrett's oesophagus and in 30.1% of the controls (p < 0.03). Type III IM at the gastric mucosa was only detected among controls. Conclusions —Barrett's oesophagus is associated with a low prevalence of H pylori cagA positive infection and multifocal atrophic gastritis. This pathobiological pattern is considered to be associated with a low risk of distal gastric cancer.